A Soul's View of the Optimal Population Problem - David de la Croix; Matthias Doepke (Institute of Labor Economics (IZA), 2021)
A long-standing challenge for welfare economics is to develop welfare criteria that can be applied to allocations with different population levels. Such a criterion is essential to resolve the optimal population problem, i.e., the tradeoff between population size and the welfare of each person alive. A welfare criterion that speaks to this issue inherently requires evaluating the welfare of nonexistent people, because some people exist only in some allocations but not in others. To make progress, we consider the population problem in an environment where population is variable, but there is a fixed supply of souls, who may experience multiple incarnations over time. Rather than pondering the value of nonexistence, from the souls' perspective comparing larger or smaller populations merely involves valuing shorter or longer waits until the next incarnation. We argue that such comparisons are possible on the basis of introspection and lead to intuitive welfare criteria with attractive properties. We emphasize that one does not have to believe in reincarnation to accept the resulting criteria—rather, reincarnation serves as a metaphor to facilitate the necessary utility comparisons.
Keywords: D63; H43; J11; Q56; 330; population ethics; repugnant conclusion; endogenous discounting; utilitarianism; reincarnation